Characterization and Maintenance of Yam (Dioscorea Spp.) Germplasm (Bangladesh Journal of Agricultural Research, 2012)
Three experiments were conducted with 60 germplasm accessions of yam (Dioscorea spp.) at Plant Genetic Resources Centre of BARI for characterization and conservation of germplasm. Fifty-nine germplasm accessions of D. alata L. and one accession of D. bulbifera L. from different  districts of Bangladesh were used. Clockwise twining direction was found in D. bulbifera and anti-clockwise twining direction was exhibited in all D. alata germplasm accessions. Potato like aerial tuber was found in D. bulbifera. Round, oval, elongate, flattened to irregular aerial tuber shape were found.  Grayed-brown, brown to grayed-orange skin colour with yellow, yellow-orange to grayed-orange of aerial tuber flesh colour were observed among the yam germplasm accessions. Oval-oblong, cylindrical, flattened, corm, rhizome to irregular shape of underground stem or tubers were observed. Low, medium to dense types of spiniess of roots were found on the tubers. Grayed-orange, red to black tuber skin colour along with white, yellowish-white, yellow, yelloworange, red to purple tuber flesh colours were found. Significant variations were also observed in stem shape at base, colour of stem, wing and petiole wing, position of leaf, leaf shape and distance between leaf lobes. Low to high phenotypic diversity was exhibited among the germplasm accessions. The germplasm accessions produced 1 to 30 under ground tubers per plant. The main tuber length ranged from 5.4 to 66.4 cm and breadth from 2.5 to 15.5 cm. The germplasm accessions produced 0.51 kg to 16.45 kg tuber yield per plant. The maximum variability was found in tuber yield per plant (98.74%) and the minimum was found in leaf length (12.55%).The under ground tubers of yam were harvested and replanted at an interval of two to three years from 1995 at PGRC. The plants were grown on bamboo trail in the field genebank. Necessary intercultural operations are done for maintaining the yam germplasm accessions. DOI: http://dx.doi.org/10.3329/bjar.v36i4.11748 Bangladesh J. Agril. Res. 36(4): 605-621, December 2011